Study of the stability of e-mode GaN HEMTs with p-GaN gate based on combined DC and optical analysis. (September 2016) - Rossetto, Isabella; Meneghini, Matteo; Rizzato, Vanessa; Ruzzarin, Maria; Favaron, Andrea; Stoffels, Steve; Van Hove, Marleen; Posthuma, Niels; Wu, Tian-Li; Marcon, Denis; Decoutere, Stefaan; Meneghesso, Gaudenzio; et al.
Abstract: This paper investigates the robustness of normally-off High Electron Mobility Transistors (HEMTs) with p-GaN gate submitted to forward gate bias overstress. By means of combined DC and spectral analysis we demonstrate the following results: (i) the devices demonstrate a time-dependent failure mechanism; (ii) time to failure (TTF) can be described by a Weibull distribution with a shape factor higher than 1, suggesting a wear-out failure; (iii) the devices have an estimated 20-years lifetime for a gate voltage of 7.2 V; (iv) TTF is temperature-dependent, with an activation energy of 0.5 eV; (v) emission microscopy reveals the presence of hot spots, whose emission originates from yellow luminescence and/or hot electron radiation. Highlights: Investigation of the stability of e-mode HEMTs with p-GaN gate to forward gate bias. Time to failure is Weibull-distributed with shape factor > 1 (wear out failure). The failure is temperature-dependent with an activation energy of 0.5 eV. A 20-years lifetime is estimated for a gate voltage of 7.2 V. Detected emission originates from yellow luminescence and/or hot electron radiation.